SOUTH AFRICA’S STRATEGIC ARMS PACKAGE: A CRITICAL ANALYSIS - Sylvester, Justin; Seegers, Annette (Scientia Militaria - South African Journal of Military Studies, 2011)
The South African government’s Strategic Arms Package (SAP), has been the largest public controversy of the post-Apartheid era. We synthesise the debates about two dimensions of the SAP, military necessity and affordability, in order to get a better understanding of civil-military relations in democratic South Africa. Our synthesis shows that the economic enthusiasm about the SAP is both naïve and an opportunity for government and dominant business and industry to wed their interests in a way that is not that different from the Apartheid era. In military terms, the SAP has equipped the South African Air Force (SAAF) and South African Navy (SAN) for the most improbable of primary missions. The equipment is also not very relevant to secondary missions. The way that the SAP decisions were reached suggests that civil-military relations are marked by the continuing impact of past compromises, corruption and the centralisation of power in the executive branch.